2003
DOI: 10.1021/jp022297o
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Calculations of the Electron Paramagnetic Resonance Parameters for VO2+ Complexes

Abstract: Density functional theory calculations of electron paramagnetic resonance (EPR) parameters, such as electronic g tensors and metal hyperfine interaction (A) tensors, have been completed for a series of VO2+ complexes. g tensors were calculated with the zeroth-order regular approximation (ZORA) for relativistic effects as incorporated into the Amsterdam Density Functional (ADF) program. The A tensors were calculated by relativistic and nonrelativistic methods as implemented in ADF and Gaussian98 programs, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 54 publications
6
39
0
Order By: Relevance
“…With DFT methods it is possible to calculate EPR parameters of transition metal complexes [22,64], and more particularly of a VO 2? species [44][45][46][47][48]. In particular, it has recently been demonstrated that it is possible to predict A z for a VO 2?…”
Section: Validation Of the Dft Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With DFT methods it is possible to calculate EPR parameters of transition metal complexes [22,64], and more particularly of a VO 2? species [44][45][46][47][48]. In particular, it has recently been demonstrated that it is possible to predict A z for a VO 2?…”
Section: Validation Of the Dft Methodsmentioning
confidence: 99%
“…As recently pointed out, the better performance of BHandHLYP than the other functionals is related to the prediction of the Fermi contact term, which depends on the indirect core level spin polarization arising from the unpaired spin density in the metal d orbitals. The spin polarization is difficult to simulate with high accuracy, and most of the functionals underestimate it significantly [45,68]. The higher fraction of Hartree-Fock exchange in half-and-half functionals such as BHandHLYP, which is available in Gaussian 03, improves considerably the prediction of the Fermi contact and, thus, of A z (see ''DFT calculations'').…”
Section: Validation Of the Dft Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently this method was used successfully for HFC tensor calculations of some vanadocene(IV) 12 and vanadyl(IV) complexes. 13,14 Calculations of HFC tensor and geometry optimizations were performed at the electron unrestricted DFT level using B3PW91 functional 23,24 with DZ basis set 25 for vanadium and pVDZ basis sets 25 for the main group atoms, according to our previous study. 12 The carbon S-HFC tensors of compounds 2 and 3 were calculated with DZ basis set for carbon of carbonate ligand and vanadium and pVDZ for the other atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Several reviews have been published on vanadium coordination chemistry, but here we emphasize those in Comprehensive Coordination Chemistry I, 1987 Since 2003 fundamental coordination chemistry continued to be developed in several fronts and theoretical studies have also improved significantly the last few years to model the structure of vanadium compounds, as well as to calculate relevant spectroscopic parameters, namely, for EPR (166,167) and NMR spectroscopies (168)(169)(170). In Chapter 22 Buhl discusses the application of DFT and QM/MM studies to models of peroxidases; already in Chapter 13 Plass and coworkers have applied DFT methods to investigate the structure of the resting state of the prosthetic group in the enzyme pocket and to elucidate the mechanism of the formation of its peroxo complex.…”
Section: Coordination Chemistrymentioning
confidence: 99%